Record of zipper loach Paracanthocobitis botia (Hamilton 1822), an ornamental fish from Paschim Medinipur, West Bengal, India - Godhuli Sit; Arun Jana; Angsuman Chanda; Sanjat Kumar Sahu (Journal of Fisheries, 2022)
Paracanthocobitis botia (Hamilton 1822) is an indigenous ornamental fish belongs to family Nemachilidae, mainly reported from north-eastern part of West Bengal. During the present survey of indigenous ornamental fish diversity in Paschim Medinipur district, P. botia has been recorded from Kangsabati River Basin (22°23¢55.0²N 87°20¢33.9²E and 22°24¢31.3²N 87°17¢54.3²E) of Midnapore, as well as Paschim Medinipur district, West Bengal. The specimens have been identified on the basis of morphometric and meristic analyses. Present study reports the extension of distribution of the species up to South-Western part of Bengal.